2018
DOI: 10.2147/ijn.s156346
|View full text |Cite
|
Sign up to set email alerts
|

A biomimetic nanoparticle-enabled toxoid vaccine against melittin

Abstract: BackgroundMelittin, the main active peptide ingredient of bee venom, can cause severe cell membrane lysis due to its robust interaction with negatively charged phospholipids. So far, no effective anti-melittin vaccine has been developed to protect people from undesired melittin intoxication.MethodsHerein, we prepared a polydiacetylene (PDA) nanoparticle with cell membrane-mimic surface to complex melittin, forming an anti-melittin vaccine (PDA–melittin).ResultsPDA nanoparticles could effectively combine with m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 34 publications
0
7
0
Order By: Relevance
“…PDA and the nano epitope peptide vaccine, nano BPP-V epitope peptide vaccine, and nano BP-IV epitope peptide vaccine were dissolved in distilled water by ultrasonication, and their morphologies, UV-vis spectra, size distributions, and zeta potentials were determined (21). The morphological characteristics were examined on a Philips CM20 transmission electron microscope (Netherlands), and the UV-vis spectra were recorded by a Perkin-Elmer Lambda 750 instrument (USA).…”
Section: Nanoparticles Characterizationmentioning
confidence: 99%
See 1 more Smart Citation
“…PDA and the nano epitope peptide vaccine, nano BPP-V epitope peptide vaccine, and nano BP-IV epitope peptide vaccine were dissolved in distilled water by ultrasonication, and their morphologies, UV-vis spectra, size distributions, and zeta potentials were determined (21). The morphological characteristics were examined on a Philips CM20 transmission electron microscope (Netherlands), and the UV-vis spectra were recorded by a Perkin-Elmer Lambda 750 instrument (USA).…”
Section: Nanoparticles Characterizationmentioning
confidence: 99%
“…Mouse serum samples were collected through tail vein from each group on days 1, 3,5,7,9,11,13,15,17,19,21,23,25,27, and 29 after immunization, and the anti-HA (IgG) antibody were determined to evaluate whether the mice consistently produce antibody. On days 7, 14, and 21 after immunization, mice serum samples were also collected through tail vein, and anti-HA antibody (IgG), IgG1, and IgG2a levels were determined by ELISA as previously described (22).…”
Section: Detection Of Specific Antibodiesmentioning
confidence: 99%
“…Nanotoxoid vaccination stimulated the host body immunity and eliminated the toxins through antigen-presenting mechanisms. Kang et al [141] reported that the nanotoxoid formation method might be a promising approach for pore-forming toxins (PFTs) vaccines. The synthetic PDA NP can efficiently neutralize melittin to reduce the toxicity of melittin.…”
Section: Applications Of Biomimetic Nanovaccinesmentioning
confidence: 99%
“…Melittin-loaded PDA NP was used as a nanotoxoid vaccination to enhance immune activity against melittin. PDA-melittin demonstrated 70% cell viability in DCs, whereas free melittin showed 90% cell apoptosis [141]. This biomimetic nanovaccine maintained the antigenic determinant of the melittin, which was responsible for high DC maturation and cellular uptake.…”
Section: Applications Of Biomimetic Nanovaccinesmentioning
confidence: 99%
See 1 more Smart Citation